2004
DOI: 10.1016/s0002-9440(10)63778-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Splicing Variants of the Human Caldesmon Gene (CALD1) in Glioma Neovascularization versus Normal Brain Microvasculature

Abstract: Caldesmon is a cytoskeleton-associated protein whichhas not yet been related to neoplastic angiogenesis. In this study we investigated the expression of the caldesmon gene (CALD1) splicing variants and the protein expression level in glioma microvessels versus normal brain microvasculature. To exclude sources of splice variant expression from non-vascular components all possible cellular components present in control and glioma samples were prescreened by laser-capture microdissection followed by RT-PCR before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 54 publications
1
50
0
Order By: Relevance
“…Moreover, CaD expression induced by p53 suppresses Src-kinase-dependent podosome formation, which inhibits fibroblast and rat aortic SMC migration (Mukhopadhyay et al, 2009). By contrast, HeLa-l-CaD expression in endothelial cells and endothelial progenitor cells in the vasculature of various human tumors promotes cell migration for vasculogenesis and angiogenesis during tumor development (Zheng et al, 2004;Zheng et al, 2007). Of note, we observed that endogenous CaD in C2C12 myoblasts localized to the membrane ruffles, suggesting that CaD is involved in cell migration in C2C12 myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CaD expression induced by p53 suppresses Src-kinase-dependent podosome formation, which inhibits fibroblast and rat aortic SMC migration (Mukhopadhyay et al, 2009). By contrast, HeLa-l-CaD expression in endothelial cells and endothelial progenitor cells in the vasculature of various human tumors promotes cell migration for vasculogenesis and angiogenesis during tumor development (Zheng et al, 2004;Zheng et al, 2007). Of note, we observed that endogenous CaD in C2C12 myoblasts localized to the membrane ruffles, suggesting that CaD is involved in cell migration in C2C12 myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, v-Src-transformed cells display a reduced expression of CALD1 (80,81), whereas v-ErbB2-transformed fibroblasts show enhanced tyrosine phosphorylation of CALD1 that correlates with stress fiber disassembly (82). Lastly, missplicing of the CALD1 gene has been observed in glioma microvasculature and is associated with tight junction breakdown between endothelial cells and vascular leakage (83). Thus, K-cyclin-induced phosphorylation of CALD1 could provide a cancer-promoting event, independent of, and in addition to, the impact of this cyclin on cell cycle progression and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…This antibody was raised against a fragment of human l-caldesmon corresponding to amino acids (aa) 251-395, a sequence 93% identical between human and mouse (Basic Local Alignment Search Tool [BLAST] analysis; Altschul et al 1997) but both present in l-and h-caldesmon. This antibody was used by Zheng et al (2004) and Bogatcheva et al (2006). K. Agassandian and Cassell (2008) used a goat anti-caldesmon (N-19) antibody raised against a peptide mapping near the N-terminus of human caldesmon (sc-7575; Santa Cruz Biotechnology, Heidelberg, Germany).…”
Section: Antibodiesmentioning
confidence: 99%
“…Some studies show caldesmon only in blood vessels, others exclusively in neurons. In the normal human brain and in gliomas, caldesmon is expressed in endothelial cells, smcs, and pericytes of blood vessels; in the dura, it is expressed in fibroblasts (Zheng et al 2003;Zheng et al 2004). In the rat cortex and hippocampus, smcs of blood vessels and endothelial cells were reported to display caldesmon immunoreactivity (Kreipke et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation